The Difference of Survival Rate COVID-19 in Patients with Initiated Hemodialysis and Regularly Hemodialysis - Viotra, Deka; Harnavi Harun; Drajad Priyono; Fauzar; Roza Kurniati; Alexander Kam; Abdul Alim Rahimi; Jersivindo Ranazeri; Zaki Mahmudi Dasril (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: Since December 2019, a novel coronavirus called SARSCoV-2 (severe acute respiratory syndrome coronavirus) has caused an international outbreak of respiratory illness described as COVID-19. This study aimed to describe the difference in the survival rate of COVID-19 induced AKI with hemodialysis and COVID-19 in patients with CKD on hemodialysis in Dr. M Djamil General Hospitals. Also, in this review, we provide a comprehensive overview of data on the factors that may be affected by COVID-19 survival rates in patients with COVID-19 induced AKI with hemodialysis and COVID-19 in patients with CKD on hemodialysis. This study was conducted to analyze the survival of COVID-19 with initiated or regular HD patients in Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This study was conducted from January 2021 to July 2021 in Dr. M. Djamil General Hospital, Padang, West Sumatera, Indonesia. Data for this study was collected through medical records of patients admitted for COVID-19 with CKD in hemodialysis and acute renal failure induced by COVID-19 to show the demographics, comorbidities, and survival rates of the patients who underwent hemodialysis. Results: Factors associated with survival in COVID-19 with hemodialysis were COVID-19 severity and abnormal potassium serum level (Table 3). Moderate COVID-19 patients tend to survive than severe COVID-19 patients (OR 60; 95% CI 16.034 – 224.525). There was no significant difference in survival between initiated and regular HD (p = 0.829). Conclusion: There is no difference in clinical outcome from patients with COVID-19 who initiated hemodialysis or regularly HD to the survival rates.